2017
DOI: 10.1016/j.supflu.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Water-gas shift reaction on alumina-supported Pt-CeO catalysts prepared by supercritical fluid deposition

Abstract: Alumina-supported platinum catalysts, both with and without ceria, were prepared by supercritical fluid deposition and evaluated for activity for water-gas shift reaction. The organometallic precursor, platinum(II) acetylacetonate, was deposited from solution in supercritical carbon dioxide. Analysis of the catalysts by high resolution scanning transmission electron microscopy indicated that platinum was present in the form of highly dispersed metal nanoparticles. Pretreatment of the alumina-supported ceria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…The use of supercritical fluid deposition (SCFD) is considered a promising catalyst preparation method, which has been recently highlighted in some studies. Deal et al synthesized platinum catalysts on alumina support, both in the presence and absence of ceria by this method and tested them for WGS reaction [39]. The result of the analysis showed Pt to be in a highly dispersed form on the support.…”
Section: Noble Metal Basedmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of supercritical fluid deposition (SCFD) is considered a promising catalyst preparation method, which has been recently highlighted in some studies. Deal et al synthesized platinum catalysts on alumina support, both in the presence and absence of ceria by this method and tested them for WGS reaction [39]. The result of the analysis showed Pt to be in a highly dispersed form on the support.…”
Section: Noble Metal Basedmentioning
confidence: 99%
“…Measuring the reaction rate confirmed that the catalyst was more active for WGS, with the rates per Pt mass exceeding the values reported in most literature for WGS reaction on the Pt-CeO x catalysts. The high catalytic activity was attributed to the considerable amount of interfacial platinum/ceria contacts due to unique nanoscale interactions [39]. Kaftan et al investigated KOHcoating Pt/alumina catalytic performance on WGS reaction [40].…”
Section: Noble Metal Basedmentioning
confidence: 99%
See 1 more Smart Citation
“…West et al reported a new generation of highly performant catalysts towards WGSR based on Al 2 O 3 -supported Pt-CeO x catalysts via supercritical fluid deposition from the organometallic precursor platinum(II) acetylacetonate. These supported Pt-CeO x catalysts featured PtNPs encapsulated in crystalline ceria and showed higher activity and greater reaction rates per mass of Pt than most literature values for WGSR on analogous Pt-CeOx catalysts [128]. Overall, these results show the great promise of SFRD as scalable means towards high performance catalysts enabling an efficient utilization of precious metals for the production of commodity gases such as H 2 [128].…”
Section: Applications In Catalysis Of Bmnps In Supercritical Fluidsmentioning
confidence: 69%
“…Then, the deposited compound is reduced to a metal either thermally, by molecular hydrogen, or by other reducing agents. As such, nanosized particles of various metals have been obtained by deposition on the surface of inorganic carriers, for example, on γ-alumina [3,4], mesoporous silicon, aluminum oxides [5][6][7], soot [8], graphene [9,10], carbon nanotubes [11,12], and aerogels [13,14]. For carriers of a polymer nature, this method has been used much less frequently.…”
Section: Introductionmentioning
confidence: 99%